Biocompatible chitosan–collagen–hydroxyapatite nanofibers coated with platelet-rich plasma for regenerative engineering of the rotator cuff of the shoulder. Issue 46 (28th August 2019) - Tang, Yi; Zhang, Hui; Wei, Qinghua; Tang, Xu; Zhuang, Wanqiang
Abstract : Over the last few decades, extraordinary progress has been accomplished in the field of bone tissue engineering. Abstract : Over the last few decades, extraordinary progress has been accomplished in the field of bone tissue engineering. Containing an incredible number of growth factors required for the process of osteogenesis, platelet-rich plasma (PRP) has gained much interest. However, because of the conflicting results obtained in various investigations, its adequacy remains a riddle. Accordingly, in this paper, we explore the in vitro application of biocompatible chitosan–collagen–hydroxyapatite (CS–COLL–HAP) nanofibers coated with platelet-rich plasma (PRP) (CS–COLL–HAP/PRP) scaffolds for the regenerative engineering of the rotator cuff (RCF) of the shoulder. FTIR spectroscopy, XRD, SEM-EDX and HRTEM were performed to evaluate the characteristics of nanofibers. After confirmation of the physicochemical properties of nanofibers, the osteogenic capability of the scaffold was assessed by measuring the relative calcium content, ALP activity, and gene expression. The results of viability and live/dead assay and cell adhesion test indicated the adequacy of the PRP when coupled with nanofibers in contrast to the other tested groups. In vivo staining affirmed increased collagen association in the PRP with nanofiber scaffolds at 30 days and 60 days. In conclusion, the addition of the PRP into CS–COLL–HAP nanofibers in this examination affected the osteogenic differentiation of osteoblast cells, and therefore, it may have an incredible perspective for bone tissue applications.